Measuring the Cognitive Workload of Working Adult Students in Batam's Higher Education Institutions: A NASA-TLX Approach - M Ansyar Bora; Ansarullah Lawi; Ririt Dwiputri Permatasari; Imam Mukhlis; Feberlian Elisabeth Gulo; Genadi Septiansyah (Jurnal Ilmu Pendidikan, 2024)
This study addresses the cognitive workload challenges faced by working adult students in Batam's higher education institutions, utilizing the NASA Task Load Index (NASA-TLX) methodology. Through a cross-sectional design and convenience sampling, data were collected from 157 part-time students across 10 universities. Results indicate that time constraints and academic effort contribute significantly to mental workload, with an average Weighted Workload (WWL) score of 68, signifying a high level of cognitive burden. Strategies for workload reduction include enhanced academic support, effective time management, and prioritizing mental well-being. This research underscores the imperative of collaborative efforts among universities, instructors, and students to cultivate an environment conducive to academic success and well-being for working adult learners.